The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/ijppm-07-2017-0168
|View full text |Cite
|
Sign up to set email alerts
|

Machine criticality based maintenance prioritization

Abstract: Purpose-The purpose of this paper is to identify the productivity improvement potentials from maintenance planning practices in manufacturing companies. In particular, the paper aims at understanding the connection between machine criticality assessment and maintenance prioritization in industrial practice, as well as providing the improvement potentials. Design/methodology/approach-An explanatory mixed method research design was used in this study. Data from literature analysis, a web-based questionnaire surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…This implies that existing assessment methods do not take a system view into consideration. Industrial practices have also shown that maintenance prioritization is not based on machine criticality (Gopalakrishnan and Skoogh 2018). In addition to the above mentioned main aspects to consider, Gopalakrishnan and Skoogh (2018) have proposed the following to address develop data-driven machine criticality assessment:…”
Section: Principles Of Machine Criticality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…This implies that existing assessment methods do not take a system view into consideration. Industrial practices have also shown that maintenance prioritization is not based on machine criticality (Gopalakrishnan and Skoogh 2018). In addition to the above mentioned main aspects to consider, Gopalakrishnan and Skoogh (2018) have proposed the following to address develop data-driven machine criticality assessment:…”
Section: Principles Of Machine Criticality Assessmentmentioning
confidence: 99%
“…Probable future scenarios for the future for maintenance organizations are to manage large volumes of data, perform data analytics, make fact-based decisions, and provide education and training, among others (Bokrantz et al 2017). The framework aligns with these probable projections to ensure that maintenance decision-making can be made on a systems-level in a way that is dynamic, fact-based and focussed on productivity (Gopalakrishnan and Skoogh 2018). Through following the principles given, the empirical research conducted in this study increases the relevance of the current problems studied and the solutions help towards narrowing the gap between maintenance theory and maintenance practice (Fraser, Hvolby, and Tseng 2015).…”
Section: Data-driven Decision Support Toolmentioning
confidence: 99%
See 2 more Smart Citations
“…At the stage of correcting production disturbances, ABC analysis is applied to prioritisation, especially for maintenance-related disturbances (Gopalakrishnan and Skoogh, 2018). In this case, the machines in production systems are classified and prioritised according to their function and impact on productivity.…”
Section: Introductionmentioning
confidence: 99%